ENT 530 Social Media Portfolio: NS Hijab / Fatin Nadira Sohairi - Sohairi, Fatin Nadira (2021)
NS Hijab is an authorised agent of Fareha. The idea of creating the business name came from the owner where NS represent Nadira Sohairi, which means to show originality and personal branding. NS Hijab provides product and service that focus on women by selling ironless printed square scarfs to Bentong people since there is no Fareha agent yet in that area. We are targeting women that aged in average of 18 to 45 years old and above. This is because the material used is super comfy and ironless that suits women who is busy as they have to juggle life between studies, work and family if they are married. The business will be formed as a sole propietorship as it the simplest and need not much document to start up. Besides, it requires only one person which is the owner herself. The shop will be opened in Bentong. It will be located at Chamang near the TF supermarket. Although it is a newly developing area, the location has shown a positive explosion of growth as it is near to residential area, schools and shoplot. NS Hijab consists of one employee named Aina to help the owner in packing orders for customers. Our employee’s drive is to provide the highest level of customer satisfaction to customers. Therefore, the product will be wrapped meticulously to ensure the product is safe during the delivery process. Other than using courier which is JnT and Poslaju to deliver the customers’ order, we also provide free cash on delivery (COD) for those who lives in Bentong and nearby areas if they purchase more than one item.